2019
DOI: 10.1088/1742-6596/1343/1/012139
|View full text |Cite
|
Sign up to set email alerts
|

BIT – Building Impulse Toolkit: a novel digital toolkit for productive, healthy and resource efficient buildings

Abstract: This paper presents the “Building Impulse Toolkit” (BIT), a novel array of digital sensors and methodologies for the transient and holistic tracking of occupant response in the built environment. BIT aims to enable the dynamic monitoring of occupant comfort, productivity and well-being in order to inform responsive and predictive control strategies. Further, to assess user experience in order to facilitate the design and operation of future resource-efficient and occupant-centred buildings. This paper describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The current version of the BIT Station interface was developed over 18 months by trials with volunteers and in collaboration with the Department of Psychology and the User Interface team at Arup. During these trials, several solution were tested as reported in a previous work [26]. The polling station format of BIT Station was selected over an alternative electronic survey with pop-up notifications because a pilot study with 16 volunteers at the University of Cambridge showed that the polling station was rated better for level of intrusiveness and the ease of use [26].…”
Section: Interfaces For Direct Occupant Feedback and Data Visualisationmentioning
confidence: 99%
See 4 more Smart Citations
“…The current version of the BIT Station interface was developed over 18 months by trials with volunteers and in collaboration with the Department of Psychology and the User Interface team at Arup. During these trials, several solution were tested as reported in a previous work [26]. The polling station format of BIT Station was selected over an alternative electronic survey with pop-up notifications because a pilot study with 16 volunteers at the University of Cambridge showed that the polling station was rated better for level of intrusiveness and the ease of use [26].…”
Section: Interfaces For Direct Occupant Feedback and Data Visualisationmentioning
confidence: 99%
“…During these trials, several solution were tested as reported in a previous work [26]. The polling station format of BIT Station was selected over an alternative electronic survey with pop-up notifications because a pilot study with 16 volunteers at the University of Cambridge showed that the polling station was rated better for level of intrusiveness and the ease of use [26].…”
Section: Interfaces For Direct Occupant Feedback and Data Visualisationmentioning
confidence: 99%
See 3 more Smart Citations